Product development from freshwater fish. - Yu, Swee Yean (1990)
The paper describes research carried out using freshwater fish in food products. Acceptable fish jelly products were developed from O. mossambicus and A. nobilis in combination with sea-water species. Proteins from O. mossambicus were hydrolysed using the enzyme alcalase in an effort to improve flavour and used in the formulation for fish crackers ('keropok'). In terms of appearance, crispiness and colour, crackers with- hydrolysate received the highest scores, compared to samples with O. mossambicus and Sciaena spp. There were no significant differences in overall acceptability in all three samples. Surimi noodles were prepared from a formulation using A. nobilis. Among these various formulations tried the formulation containing 25 parts tapioca flour and 2 parts sodium tripolyphosphate was most acceptable to taste panelists.